2022
DOI: 10.3390/jpm12071067
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Personalized Psychiatric Therapy with the Example of Using Intranasal Oxytocin in PTSD Treatment

Abstract: Post-traumatic stress disorder (PTSD) is a severe mental disorder that results in the frequent coexistence of other diseases, lowers patients’ quality of life, and has a high annual cost of treatment. However, despite the variety of therapeutic approaches that exist, some patients still do not achieve the desired results. In addition, we may soon face an increase in the number of new PTSD cases because of the current global situation—both the COVID-19 pandemic and the ongoing armed conflicts. Hence, in recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 96 publications
0
3
0
1
Order By: Relevance
“…Another candidate is the nonapeptide oxytocin, a hormone with multiple functions including social bonding, reproduction, and childbirth [ 108 ]. Recent studies have shown that oxytocin treatment may play a role in improving autism [ 109 ] and other mental disorders such as post-traumatic stress disorder (PTSD) [ 110 ]. Relatively larger peptides such as leptin may be also relevant targets of baculovirus display.…”
Section: Discussionmentioning
confidence: 99%
“…Another candidate is the nonapeptide oxytocin, a hormone with multiple functions including social bonding, reproduction, and childbirth [ 108 ]. Recent studies have shown that oxytocin treatment may play a role in improving autism [ 109 ] and other mental disorders such as post-traumatic stress disorder (PTSD) [ 110 ]. Relatively larger peptides such as leptin may be also relevant targets of baculovirus display.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid anxiolytic effects of intranasal oxytocin have been observed in non-clinical human participants, albeit in a manner dependent upon the chronicity of administration and inter-individual variables including age, gender and psychosocial functioning ( Naja and Aoun, 2017 ; Neumann and Slattery, 2016 ). Variability in response magnitude across individuals has also characterized the behavioral and neural (e.g., amygdala and PFC activity) effects of intranasal oxytocin in small-scale PTSD studies to-date (reviewed in ( Peled-Avron et al, 2020 ; Sandra Szafoni, 2022 )). These findings raise questions about the broad applicability of oxytocin as a treatment for PTSD, though a more positive take is that oxytocin may be suited to more personalized medicine.…”
Section: Neuropeptides: a Nose For Neuromodulationmentioning
confidence: 99%
“…Основу сучасних підходів до діагностики та корекції психологічних наслідків війни становить концепція відстрочених реакцій на травматичний стрес [7]. Особливу увагу приділяють посттравматичному стресовому розладу (ПТСР), що призводить до частого співіснування з іншими захворюваннями, знижує якість життя пацієнтів та потребує високих щорічних витрат на лікування [8]. З часом нас очікує збільшення числа нових випадків посттравматичного стресу через поточну глобальну ситуацію -пандемію COVID-19 і збройні конфлікти, що продовжуються [7].…”
Section: вступunclassified